Influence of Parenting Styles on Students’ Performance under Modular Distance Learning - Casinillo, Leomarich F; Agravante, Nicolle; Baldevia, Athena Claire N.; Tang, Erin Chanelle O. (Indonesian Journal of Educational Research and Review, 2023)
The influence of parents on their children is vital in that it molds a cognitive behavior that will reflect on their academic performance. During the COVID-19 pandemic, high school students have to learn in the form of modular learning in which they were just in their respective homes and their parents were taking the role of school teacher. This study aimed to evaluate the influence of different parenting styles of parents on the student's performance under modular distance learning amid the lockdown of the pandemic. Primary data were collected from 87 high school students who responded to the Google survey such as profiles of students, grades, and parenting styles using the Parental Authority Questionnaire (PAQ). The data gathered were analyzed through standard descriptive measures and correlational analysis. Results depicted that, on average, students have a "very satisfactory" performance, that is, the grade point average is 93%. Moreover, students' mothers and fathers are both "authoritative" in their education. Based on the correlation analysis, the mother's strictness (opposite of permissive (p-value=0.027) can positively influence the student's academic achievement, but the relationship is revealed to be weak. In addition, the fathers' parenting styles have no association with their children's academic performance based on the correlation analysis (p-values>5%). This implies that most of the time students are learning independently from their respective parents at home. Hence, most of the high school students during modular learning amid the pandemic are learning without the aid and influence of their parents.